Misleading Diagnosis of Radiological Imaging of COVID-19 Pneumonia During Pandemic Era: Risk on the Existence of CMV Infection - Ceva Wicaksono Pitoyo; I Putu Eka Krisnha Wijaya; Vally Wulani; Anindita Kartika Wiraputri; Michael Aaron Romulo (Interna Publishing, 2020)
Coronavirus disease 2019 (COVID-19) is an acute respiratory disease which rapidly disseminated due to Severe Acute Respiratory Syndrome CoronaVirus-2 (SARS-CoV-2) virus. Clinical presentations of COVID-19 are fever, non-productive cough, and dyspnea. Although the diagnosis establishment is done by detecting the viral ribonucleic acid (RNA) through reverse transcription-polymerase chain reaction (RT-PCR) method, CT scan has an important role in detection and treatment of COVID-19 especially in high prevalence regions. Chest CT scan has high sensitivity yet low specificity because there are a lot of other pathological spectrums that also present features of COVID-19 such as ground glass opacities (GGO) and consolidation, one of them is CMV infection. The objective of this case report is to raise vigilance towards other diseases that have radiological image similarities with COVID-19, especially in the immunocompromised patients who are susceptible to viral infections like CMV infection so that the delay in the disease treatment can be prevented.